(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2026)
One of the greatest problems of the current service sector management is ensuring and sustaining the client happiness. Service quality and customer happiness have become more important as a major differentiator and a driver of retention in the continuous war for market share. A poll indicates that professionals in the tourism and hospitality sectors have grown more aware of the fact that customers have placed an unprecedented demand for high quality goods and services in recent years. The necessity to provide excellent levels of customer service is universally recognized as a fundamental ingredient in any business’s success.